Preparation of Modified Corn Straw Cellulose and Its Effect on the Stability of Pickering Emulsion - Tian SHAO; Hongxiu FAN; Bingli LIU; Xu TENG; Tingting LIU; Yanrong ZHANG (Shipin gongye ke-ji, 2023)
The corn straw cellulose (CS) was extracted from corn straw by sodium chlorite-acetic acid-sodium hydroxide method, and modified by sulfuric acid hydrolysis and sulfuric acid hydrolysis-high pressure homogenization, respectively. Pickering emulsion was prepared by thyme essential oil as oil phase. The effect of cellulose as emulsifier on the stability of Pickering emulsion before and after modification was studied. The structure and properties of the cellulose before and after modification were characterized, and the microstructure, particle size, potential, stability and rheological properties of the emulsion were measured. The results showed that: Compared with CS and sulfuric acid hydrolyzed cellulose (CP), the particle size of the modified cellulose, which was hydrolyzed with sulfuric acid and homogenized under high pressure (HPC) was significantly decreased (P<0.05) to 28.61 µm. The number of active groups increased, and the hydrostatic contact angle increased to 76.1°, about 2.4 times of CS. The microstructure of CP showed short rod-like structure and smooth surface. On the other hand, HPC had a curly surface, which changed from smooth to loose and porous. The stability of Pickering emulsion was improved by modified corn straw cellulose. The emulsion stabilized by HPC had the best stability, with the smallest particle size (3.53 µm) and more uniform particle size distribution. Store at 25 ℃ for 21 days, there was no obvious flocculation between droplets, and the TSI value changed the least (0.359), showing good storage stability. These results proved that the emulsification property of HPC was enhanced compared with CS and CP, which provided a theoretical basis for corn straw cellulose to be used as food grade solid emulsifier and realized high value utilization of corn by-products.